Isolation of an unusual [Cu6] nanocluster through sequential addition of copper(i) to a polynucleating ligand. Issue 7 (30th January 2017) - Phanopoulos, Andreas; Warren, Mark; White, Andrew J. P.; Horton, Andrew; Crimmin, Mark R.
Abstract : Addition of 2 equiv. of CuI to a [Cu]4 multimetallic complex results in cluster formation leading to the isolation of a rare bicapped tetrahedral [Cu6 I2 ] cluster that is stabilised by two conformationally constrained polynucleating ligands. Abstract : Addition of 2 equiv. of CuI to a [Cu]4 multimetallic complex results in cluster formation leading to the isolation of a rare bicapped tetrahedral [Cu6 I2 ] cluster that is stabilised by two conformationally constrained polynucleating ligands.